Efektivitas Sistem Pengarsipan: Manfaat Chronological Filing System dan Numerical Filing System pada Dokumen Transaksi Perusahaan - Liana Suryaningsih; Putri Nursyahbani Widia; Siti Fatimah; Tutik Setyoningsih; Binti Muchsini (BADAN PENERBIT STIEPARI PRESS, 2023)
Records management has a significant impact on the smooth running of administration. Inaccuracy in records management can cause detrimental problems for the organization. Archives management at PT Jamkrindo is still experiencing several problems. Several transaction files and credit guarantee files have piled up so that many files are lost and hidden. Many archives have not been managed well in work units. Archives still appear to be mixed between archives that are still needed (active archives) and archives that are no longer needed (inactive archives). The purpose of this activity is to find out the extent of the effectiveness of the Filing System: Benefits of the Numerical Filing System (Number System) in PT Jamkrindo Solo Branch Transaction Documents. This research uses observation, literature study and design methods. The results of the activity show that based on a literature study conducted regarding archive management, a filing system was found that could be implemented by PT Jamkrindo Solo Branch, namely by implementing a filing system based on chronological filing system and numbers (numerical filing system.